Development of a novel nomogram for predicting ongoing pregnancy after in vitro fertilization and embryo transfer - Kim, Seul Ki (Obstet Gynecol Sci, 2018)
OBJECTIVE: This study aimed to develop a nomogram that predicts ongoing pregnancy after in vitro fertilization and embryo transfer (IVF-ET) using patient age and serum hormonal markers. METHODS: A total of 284 IVF-ET cycles were retrospectively analyzed. At 14 days post-oocyte pick-up (OPU), the serum human chorionic gonadotropin (HCG) and progesterone levels were measured. The main predicted outcome was ongoing pregnancy. RESULTS: Patient age and serum of HCG and progesterone levels at 14 days post-OPU were good predictors of ongoing pregnancy. The cut-off value and area under the curve (AUC) (95% confidence interval) were 36.5 years and 0.666 (0.599–0.733), respectively, for patient age; 67.8 mIU/mL and 0.969 (0.951–0.987), respectively, for serum HCG level; and 29.8 ng/mL and 0.883 (0.840–0.925), respectively, for serum progesterone level. When the prediction model was constructed using these three parameters, the addition of serum progesterone level to the prediction model did not increase its overall predictability. Furthermore, a high linear co-relationship was found between serum HCG and progesterone levels. Therefore, we developed a new nomogram using patient age and HCG serum level only. The AUC of the newly developed nomogram for predicting ongoing pregnancy after IVF-ET cycles using patient age and serum HCG level was as high as 0.975. CONCLUSION: We showed that ongoing pregnancy may be predicted using only patient age and HCG serum level. Our nomogram could help clinicians and patients predict ongoing pregnancy after IVF-ET if the serum JCG level was ≥5 IU/L at 14 days post-OPU.